(untitled) (PerCursos, 2024)
This article examines the album About kids, hips, nightmares and homework, released by Emicida in 2015. Through analyses, we sought to point out the ways in which the so-called new condition of rap (Santos, 2022) is formalized in the constituent elements of the album as a whole, as well as within its tracks. We recognized that the experience of the African diaspora constitutes the core of the album. More specifically, we observed that the album brings a balance between compositions that denounce the oppression suffered by the black population and, on the opposite pole, tracks that approach blackness from a celebratory and uplifting perspective. In turn, such themes correspond, on the one hand, to the use of sounds that are more aggressive and, on the other, to greater delicacy and lightness of sound, both in the singing and in the musical base. We also found different ways of singing, some very close to orality itself and others with greater musical formalization. In summary, we discussed that the diversity of themes and sounds present on the album is compatible with the expansion of rap’s audience, something constitutive of its contemporary condition, and that this lies both its strength and the limit of its criticism.